Fashion through history : costumes, symbols, communication - Motta, Giovanna; Biagini, Antonello (Fashion through history., 2017)
This collection arises from an international fashion conference held at Sapienza University in Rome, Italy, in May 2015. It is dedicated to one of the main indicators of social change, fashion, analysed within various scientific fields, historical periods, and geographical areas.